Back Cover: Bottom‐Up Synthetic Biology: Towards the Modular Design of Artifical Cells from Functional Modules (Adv. Biosys. 6/2019). Issue 6 (13th June 2019) - Landfester, Katharina; Sundmacher, Kai
Abstract : A bottom‐up strategy allows for better control of the complexity of the objects of investigation, particularly the number of system components and the number of interactions, than experiments performed in a topdown manner. Thus, new combinations of natural and non‐natural molecules can be studied. The authors hope that the articles herewith would inspire readers when thinking about new artificial cellular systems with exciting properties.